Pergeseran Partisipasi Sosial (Masyarakat) dalam Masa Pandemi COVID-19 (Tinjauan Fenomenologis Individu Selama Pandemi COVID-19) - Kurniawan, Ignasius Putra (Jurnal Kewarganegaraan, 2022)
AbstractIn this study, my research theme focuses on the phenomenon of Indonesian individual social involvement in responding to the reality of the COVID-19 pandemic. If in normal situations, individual involvement in society looks active. The encounter between individuals becomes a tangible form of the involvement and presence of individuals in society. The focus of this study is to look at the different meanings of the presence and involvement of individuals in society during a pandemic. Each individual can participate in society through their ways. This research study uses a literature methodology. This method is carried out by exploring the phenomena that occur in the community during this pandemic. The finding in this study is the phenomenon of the presence of individuals in a limited society. Limited encounters between individuals remain a form of social engagement but in a different way. Thus, the term "people lying down" was born amid Indonesian society. Real presence is no longer face-to-face, but each struggle for the common good. Thus, the final goal achieved remains the same, but the means and expressions of participation have differences.-----------AbstrakDalam studi ini fokus tema penelitian saya ialah pada fenomena keterlibatan sosial individu Indonesia dalam menanggapi realitas pandemi COVID-19. Jika dalam situasi normal, keterlibatan individu dalam sosial terlihat aktif. Perjumpaan antar individu menjadi bentuk nyata dari keterlibatan dan kehadiran individu dalam masyarakat. Fokus studi ini ialah melihat perbedaan makna kehadiran dan keterlibatan individu dalam sosial selama masa pandemi. Masing-masing pribadi dapat berpartisipasi dalam sosial melalui cara-caranya masing-masing. Studi penelitian ini menggunakan metodologi kepustakaan. Metode ini dilakukan dengan menggali fenomena-fenomena yang terjadi di masyarakat selama masa pandemi ini. Temuan dalam studi ini adalah fenomena kehadiran individu dalam sosial secara terbatas. Perjumpaan antar individu yang terbatas, tetap menjadi bentuk keterlibatan sosial namun dengan cara yang berbeda. Sehingga lahirlah istilah kaum rebahan di tengah sosial Indonesia. Kehadiran nyata bukan lagi bertemu secara langsung, tetapi berjuang masing-masing demi kebaikan bersama. Dengan demikian, tujuan akhir yang dicapai tetap sama, namun cara dan ungkapan partisipasi memiliki perbedaan.